Optical waves solutions for the perturbed Fokas-Lenells equation through two different methods - Ali, Karmina K.; Yusuf, Abdullahi; Yokus, Asif; Ali, Mohamed R. (Elsevier, 2023)
This study examines the perturbed Fokas-Lenells equation using two methods: the Bernoulli sub-equation function method and the (1/G ')-expansion method. A traveling wave transformation is used to convert the governing equation into a nonlinear ordinary differential equation. The perturbed Fokas-Lenells equation arises in optical fibers, and the article constructs various optical soliton solutions, including periodic dark-bright, singular, and periodic singular soliton solutions. The article also presents the necessary constraint conditions for the existence of valid solitons and graphs 2D, 3D, and contour surfaces based on different parameter values.
Keywords: Optical soliton solutions; The perturbed Fokas-Lenells equation; The Bernoulli sub-equation function method; The(1/G')-expansion method